Determination of pantoprazole in human plasma by LC-MS-MS using lansoprazole as internal standard - Peres, O.; Oliveira, C. H.; Barrientos-Astigarraga, R. E.; Rezende, V. M.; Mendes, G. D.; Nucci, G. de (Ecv-editio Cantor Verlag Medizin Naturwissenschaften, 2004)
An analytical method based on liquid chromatography with positive ion electrospray ionization (ESI) coupled to tandem mass spectrometry detection was developed for the determination of pantoprazole (CAS 102625-70-7) in human plasma using lansoprazole (CAS 103577-45-3) as the internal standard. The analyte and internal standard were extracted from the plasma samples by liquid/liquid extraction using diethyl-ether/dichloromethane (70:30; v/v) and chromatographed on a C-8 analytical column. The mobile phase consisted of acetonitrile/water/methanol (57:25:18; v/v/v) + 10 mmol/l acetic acid + 20 mmol/l ammonium acetate. The method has a chromatographic total run time of 4.5 min and was linear within the range 5.0-5,000 ng/mL. Detection was performed on a triple quadrupole tandem mass spectrometer by Multiple Reaction Monitoring (MRM). The intra- and inter-run precisions calculated from quality control (QC) samples were 4.2% and 3.2%, respectively. The accuracies as determined from QC samples were -5.0% (intra-run) and 2.0% (inter-run). The method herein described was employed in a bioequivalence study of two tablet formulations of pantoprazole.
Keywords: CAS 102625-70-7; pantoprazole, determination in human plasma; proton pump inhibitor